Sistem Informasi Pendaftaran Peserta Didik Baru Sekolah Dasar Negeri I Wotgali - Rahmat Mauludin; Dita Rizki Amalia; Raditya Danar Dana; Saeful Anwar (Ma'soem University, 2022)
The problem that occurs at the State Elementary School 1 Wotgali is that the registration process for new students is still manual, so prospective students sometimes have difficulty getting information to carry out the registration process. This study uses the waterfall method, coding at this stage the author designs the database and interface in the programming language using html, php and css languages. The purpose of this study is to build a computerized New Student Admission Information System. With the creation of this information system, it is hoped that data input, registrant data filtering, are carried out more practically. Faster search and presentation of information, thereby increasing effectiveness and minimizing errors that have occurred before. The test results show the application runs well from registration, registration confirmation, and print registration.